ASPECTOS JURÍDICOS DA PERSONIFICAÇÃO DOS ALGORITMOS DIGITAIS E SUA CAPACIDADE DE RESPONSABILIZAÇÃO CIVIL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The use of Artificial Intelligence Algorithms occurs in people's lives without them even realizing it. Algorithms have moved from basic calculations to controlling almost every aspect of human life. Its use ranges from recommendations on what type of content people will see on their social networks, to machines such as self-driving cars. In this sense, we need to understand the role of law, visualizing the possibility or not of personification of these artificial intelligence algorithms, so that we can assign responsibility to these entities. We will also see in this work the role of important legislation, such as the GDPR at the European level and the “Marco Civil da Internet” and the LGPD in Brazil. We will also analyze European Parliament resolutions that propose both the personification and accountability of the holders of artificial intelligence algorithms. We will thus present what the possibility of accountability is found today in legislation and whether personification would be an effective way out for current legislation. The methodology that was applied was documental, bibliographic and even jurisprudential research. With this research method, the premises that guide the theme will be studied.